IMPLEMENTASI SISTEM AKUNTABILITAS KINERJA INSTANSI PEMERINTAH DESA (SAKIP DESA) KABUPATEN SUMEDANG - arip rahman sudrajat; Helga Ardiani Fauziah; Jehan Arizal Diliya; Reni Rosmawati; Syiffa Nurul Amallia; Wanda Himatul Aliyah; Widia Rahayu (LPPM UNSAP & FISIP UNSAP, 2022)
The SAKIP Desa policy is carried out by the village government to measure success and create a government that has the capacity and accountability for village performance. The implementation of SAKIP Desa in government agencies includes planning, implementing, measuring and monitoring performance as well as reporting performance to higher institutions. SAKIP Desa is an integration of the planning system, budgeting system and performance reporting system, which is in line with the implementation of the financial accountability system. In SAKIP Desa in Sumedang Regency, there are three main priorities, namely reducing poverty, reducing stunting, and increasing the Community Satisfaction Index (IKM). The research method used in this study is a qualitative research method with a descriptive type of research. The technique used in determining the target of research informants used purposive sampling technique. Data collection techniques were carried out by means of library research and field studies, namely by conducting observations, interviews and documentation. The SAKIP Desa policy at the Sumedang Regency Community and Village Empowerment Service (DPMD) has been going quite well. However, in its implementation there are still several obstacles, one of which is because the available human resources are still limited and have not been able to fully understand how to implement the online-based SAKIP Desa policy (e-sakip), so the results obtained are not in accordance with the actual data.